A New Look on Octet‐Compliant Macrocyclic Organoaluminum Carboxylates as Dormant Poly‐Lewis Acids. Issue 1 (23rd December 2019) - Terlecki, Michał; Justyniak, Iwona; Prochowicz, Daniel; Lewiński, Janusz
Abstract : A more in‐depth understanding of the multi‐faceted chemistry of organoaluminum complexes is continually vital for the comprehension and development of new reagents and catalytic systems as well as molecular building blocks for modern functional materials. In this report we utilize a macrocyclic tetranuclear organoaluminum derivative of 2, 3‐naphthalenedicarboxylic acid ( naphtha ‐H2 ), [(Me2 Al)2 ( naphtha )]2, as a model complex to probe both the dormant Lewis acidity and self‐assembly processes of octet‐compliant multinuclear macrocyclic organoaluminum compounds in the presence of mono‐ or bidentate pyridine ligands. The results nicely demonstrate that multinuclear octet‐compliant organoaluminum clusters may effectively act as so‐called poly‐Lewis acids, utilizing their dormant Lewis acidity with the preservation or cleavage of the parent macrocycle depending on the character of both donor ligands and aromatic subunits of the dicarboxylate ligands. Abstract : We report on a macrocyclic tetranuclear organoaluminum derivative of 2, 3‐naphthalenedicarboxylic acid, and its unique and contrasting molecular and supramolecular complexes with various pyridine and bipyridines. The results demonstrate that multinuclear octet‐compliant organoaluminum clusters may effectively act as PLA, utilizing their dormant Lewis acidity.